2011
DOI: 10.1186/1471-2458-11-794
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of coexisting prehypertension and prediabetes among healthy adults in northern and northeastern China

Abstract: BackgroundPrehypertension and prediabetes are major risk factors of cardiovascular disease, and their combined presence may result in more serious cardiovascular outcomes than expected with either prehypertension or prediabetes alone. The aim of the present study was to evaluate the prevalence of coexisting prehypertension and prediabetes, and the associated risk profiles in a Chinese population.MethodsA cross-sectional survey in a representative sample of 3,595 men and 4,593 women aged 18 years and older was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
3
15
0
1
Order By: Relevance
“…Prehypertension and hypertension were associated in most cases with at least two additional cardiovascular risk factors thus enhancing the odds to develop cardiovascular events [9] [19] [20] [42] [43]. The risk in subjects with prehypertension has been attributed to endothelial dysfunction, increased level of pro-inflammatory cytokines and gamma glutamyl-transferase, oxidative stress, and structural remodelling of the myocardium in comparison to subjects with blood pressure in the normal range [9] [23] [44]- [47]. Unlike other studies [11] [37] [48] [49] the rates of diabetes mellitus were similar in our three blood pressure categories whereas in accordance with most reports [18] Our results should be interpreted within the limitations of the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Prehypertension and hypertension were associated in most cases with at least two additional cardiovascular risk factors thus enhancing the odds to develop cardiovascular events [9] [19] [20] [42] [43]. The risk in subjects with prehypertension has been attributed to endothelial dysfunction, increased level of pro-inflammatory cytokines and gamma glutamyl-transferase, oxidative stress, and structural remodelling of the myocardium in comparison to subjects with blood pressure in the normal range [9] [23] [44]- [47]. Unlike other studies [11] [37] [48] [49] the rates of diabetes mellitus were similar in our three blood pressure categories whereas in accordance with most reports [18] Our results should be interpreted within the limitations of the present work.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we observed higher GGT and UA levels in subjects with coexisting prehypertension and prediabetes, which suggests that GGT and UA are associated with prediabetes [11]. Similarly, results of several surveys conducted in the United States and other countries implicated GGT and/or UA in the development of diabetes [12-15].…”
Section: Introductionmentioning
confidence: 88%
“…The data used in this study are from the Chinese Physiological Constant and Health Condition (CPCHC) survey. This research used a multistage, random, stratified sampling method to obtain a nationally representative sample of the general Chinese population 18 , 19 . In brief, 6 provinces (Sichuan-Southwest, Yunnan-South, Hunan-South, Inner Mongolia Autonomous Region-North, Ningxia Hui Autonomous Region-Northwest, and Heilongjiang-Northeast) were selected from different geographical regions in China.…”
Section: Methodsmentioning
confidence: 99%